A systematic review of [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/CT in the diagnostic value of malignant tumor bone metastasis - Li, Lanying; Hu, Xin; Ma, Jiao; Yang, Songsong; Gong, Weidong; Zhang, Chunyin (Frontiers in Oncology, 2022)
Objective: To perform a systemic analysis of [68Ga]Ga-DOTA-FAPI-04 positron emission tomography (PET)/computerized tomography (CT) and [18F]FDG PET/CT for the diagnosis of malignant tumor bone metastasis based on the existing clinical evidence. Methods: This systematic review followed the guidelines of the Preferred Reporting Project (PRISMA) for systematic reviews and meta-analysis. This is a retrospective study of articles published in PubMed. EMBASE was searched online from the start of May 2022. The main endpoints were the maximum standardized uptake value and tumor-to-background ratio to determine the examination performance of [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG for bone transfer stoves. Based on the entry and discharge standards, two researchers extracted documents and data and then performed the quality evaluation. Results: A total of 8 studies were included on the metastasis of malignant tumor bone, which involved 358 patients in the final analysis. Conclusion: [68Ga]Ga-DOTA-FAPI-04 showed better detection performance for bone metastasis. The sensitivity of [68Ga]Ga-DOTA-FAPI-04 for the diagnosis of the primary tumor was higher than that of [18F]FDG, whereas the specificity of [18F]FDG was higher than that of [68Ga]Ga-DOTA-FAPI-04. However, further randomized controlled trials and prospective clinical trials are warranted to compare the diagnostic performance of [68Ga]Ga-DOTA-FAPI-04 PET/CT and [18F]FDG PET/CT.